Asymmetric synthesis of a highly functionalized bicyclo[3.2.2]nonene derivative - Tabuchi, Toshiki; Urabe, Daisuke; Inoue, Masayuki (Beilstein Journal of Organic Chemistry, 2013)
The stereoselective Diels–Alder reaction between an optically active 1,4-dimethylcycloheptadiene and acrolein was effectively promoted by TBSOTf to produce a bicyclo[3.2.2]nonene derivative bearing two quaternary carbons. Seven additional transformations from the obtained bicycle delivered the C2-symmetric bicyclo[3.3.2]decene derivative, a key intermediate in our synthetic study of ryanodine.
Keywords: asymmetric synthesis; C2-symmetry; catalysis; Diels–Alder reaction; Lewis acid; natural product; quaternary carbon

(untitled) - Rogers, E. F.; Koniuszy, F. R.; Shavel, J., Jr; Folkers, K. (J. Am. Chem. Soc., 1948)

(untitled) - Wiesner, K.; Valenta, Z.; Findlay, J. A. (Tetrahedron Lett., 1967)

(untitled) - Srivastava, S. N.; Przybylska, M. (Can. J. Chem., 1968)

(untitled) - Betzenhauser, M. J.; Marks, A. R. (Pfluegers Arch., 2010)

(untitled) - Mackrill, J. J. (Biochem. Pharmacol., 2010)

(untitled) - Bélanger, A.; Berney, D. J. F.; Borschberg, H.-J.; Brousseau, R.; Doutheau, A.; Durand, R.; Katayama, H.; Lapalme, R.; Leturc, D. M.; Liao, C.-C.; MacLachlan, F. N.; Maffrand, J.-P.; et al. (Can. J. Chem., 1979)

(untitled) - Deslongchamps, P.; Bélanger, A.; Berney, D. J. F.; Borschberg, H.-J.; Brousseau, R.; Doutheau, A.; Durand, R.; Katayama, H.; Lapalme, R.; Leturc, D. M.; Liao, C.-C.; MacLachlan, F. N.; et al. (Can. J. Chem., 1990)

(untitled) - Sieburth, S. M.; Santos, E. D. (Tetrahedron Lett., 1994)

(untitled) - Wood, J. L.; Graeber, J. K.; Njardarson, J. T. (Tetrahedron, 2003)

(untitled) - Urabe, D.; Nagatomo, M.; Hagiwara, K.; Masuda, K.; Inoue, M. (Chem. Sci., 2013)

(untitled) - Hagiwara, K.; Himuro, M.; Hirama, M.; Inoue, M. (Tetrahedron Lett., 2009)

(untitled) - Iwatsu, M.; Urabe, D.; Inoue, M. (Heterocycles, 2010)

(untitled) - Spahić, B.; Thu, T. T. M.; Schlosser, M. (Helv. Chim. Acta, 1980)

(untitled) - Guo, M.; Minuti, L.; Taticchi, A.; Wenkert, E. (J. Org. Chem., 1990)

(untitled) - Barbot, F.; Mesnard, D.; Miginiac, L. (Org. Prep. Proced. Int., 1978)

(untitled) - Cane, D. E.; Thomas, P. J. (J. Am. Chem. Soc., 1984)

(untitled) - Demole, E.; Enggist, P.; Borer, M. C. (Helv. Chim. Acta, 1971)

(untitled) - Marcos, I. S.; Oliva, I. M.; Moro, R. F.; Díez, D.; Urones, J. G. (Tetrahedron, 1994)

(untitled) - González, A. G.; Darias, J.; Martin, J. D.; Melián, M. A. (Tetrahedron Lett., 1978)

(untitled) - Brown, H. L.; Buchanan, G. L.; O’Donnell, J. (J. Chem. Soc., Perkin Trans. 1, 1979)

(untitled) - Nakashima, K.; Inoue, K.; Sono, M.; Tori, M. (J. Org. Chem., 2002)

(untitled) - Krafft, M. E.; Holton, R. A. (Tetrahedron Lett., 1983)

(untitled) - Corey, E. J.; Shibata, S.; Bakshi, R. K. (J. Org. Chem., 1988)

(untitled) - Ohtani, I.; Kusumi, T.; Kashman, Y.; Kakisawa, H. (J. Am. Chem. Soc., 1991)

(untitled) - Lamy-Schelkens, H.; Giomi, D.; Ghosez, L. (Tetrahedron Lett., 1989)

(untitled) - Lamy-Schelkens, D.; Ghosez, L. (Tetrahedron Lett., 1989)

(untitled) - Hua, Z.; Chen, L.; Mei, Y.; Jin, Z. (Tetrahedron Lett., 2009)

(untitled) - Greenhouse, R.; Borden, W. T.; Ravindranathan, T.; Hirotsu, K.; Clardy, J. (J. Am. Chem. Soc., 1977)

(untitled) - Krow, G. R. (Tetrahedron, 1987)